Volunteer Camp: First Aid Training Program And Positive Behavior Of Youth Students In Plantation Schools Area, Malang District: Volunteer Camp: Program Pelatihan Pertolongan Pertama Dan Perilaku Positif Pada Remaja Siswa Yang Sekolah Di Wilayah Perkebunan, Kabupaten Malang (JURNAL UNEJ, 2023)
Accidents such as falls and animal stings and bites are often encountered by students who attend school in plantation areas. Apart from that, bad behavior, such as not going to school because of harvesting activities and planting sugarcane, is a problem in schools in plantation areas. Teenagers are one of the agents of change who are able to be examples and peers in the school environment. Therefore, efforts that can be made with first aid training and positive behavior for students who study in plantation areas. The Volunteer Camp program is an innovation program with the aim of improving the spirit of young volunteers and being able to carry out promotive and preventive efforts in first aid and positive behavior in adolescent students. This program was implemented at Jendral Soedirman Kalipare High School and was attended by school representatives from Bantur, Donomulyo and Kalipare sub-districts. The program was implemented in September 2022 with an assessment program, outreach to partners, a volunteer camp program (first aid and positive behavior training), and program evaluation. The instrument used was a first aid knowledge questionnaire, first aid check list and positive behavior. The result was an increase in partner knowledge before (61.18 ± 12.45) and after (82.01 ± 9.93) first aid training. The next results are simulations of first aid performed by partners on average (67 ± 13.05) and simulations of positive behavior on average (78 ± 11.56). The conclusion from the results of community service is that partners experience an increase in knowledge about first aid, partners have sufficient value in conducting first aid simulations and are good at simulating positive behavior.